Mechanistic insight into the interaction of gastrointestinal mucus with oral diblock copolymers synthesized via ATRP method - Liu, Jiao (Int J Nanomedicine, 2018)
INTRODUCTION: Nanoparticles are increasingly used as drug carriers for oral administration. The delivery of drug molecules is largely dependent on the interaction of nanocarriers and gastrointestinal (GI) mucus, a critical barrier that regulates drug absorption. It is therefore important to understand the effects of physical and chemical properties of nanocarriers on the interaction with GI mucus. Unfortunately, most of the nanoparticles are unable to be prepared with satisfactory structural monodispersity to comprehensively investigate the interaction. With controlled size, shape, and surface chemistry, copolymers are ideal candidates for such purpose. MATERIALS AND METHODS: We synthesized a series of diblock copolymers via the atom transfer radical polymerization method and investigated the GI mucus permeability in vitro and in vivo. RESULTS: Our results indicated that uncharged and hydrophobic copolymers exhibited enhanced GI absorption. CONCLUSION: These results provide insights into developing optimal nanocarriers for oral administration.